Pengembangan Modul Ajar Interaktif Berbasis Augmented Reality Materi Sistem Tata Surya Untuk Meningkatkan Self Esteem Siswa Kelas VI - Hidayatul Isnaini; Mohammad Fatih; Cindya Alfi (Pusat Riset dan Inovasi Nasional, 2024)
The development of science and technology is increasingly encouraging efforts to update the way technology is used in the educational process. Teachers must be able to utilize current technology to help students learn. There are many kinds of media in learning, for example real or technology-based media. One type of technology-based media is augmented reality. The aim of this research is to find out how to create and use interactive teaching modules based on augmented reality, and whether this module can increase students' self-esteem in class VI of SD Negeri Kendalrejo Srengat, Blitar Regency. This research uses research and development (R & D) with the ADDIE method, which consists of analysis, design, development, implementation and evaluation. The validation results of the product assessment by material experts obtained a percentage of 92 percent with the criteria